Impact of Road Crashes on Poverty in Myanmar: A Case Study in Yangon (Global Journal of Human-Social Science, 2019)
This paper reveals the impacts of road crashes on poor people in Yangon Myanmar The study aims to investigate whether poor people are more likely to be involved in road crashes and to identify whether the consequences of road crashes have higher impacts on poor households than on non-poor households The study was based on a questionnaire survey conducted in Yangon To identify involvement in road crashes and impacts on the households of poor and non-poor people hypothesis tests were applied A linear regression model and logit model were applied to evaluate contributing factors to a declining situation of household income after road crash involvement The results show that lower social economic groups are more involved in road crashes in Yangon than are higher social economic groups The costs and impacts of road crashes are higher burdens for poor people The findings can assist policy makers in determining appropriate policies to mitigate the impacts and improve poverty alleviation actions Other than that transportation planning such as the improvement of public transport and basic road infrastructure could reduce the road crash problem for poor people who are the main group of road users in Yangon
Keywords: road crashes; poverty; yangon; myanmar